Crisis política y populismo militar en el Perú - Cotler, Julio (Estudios Internacionales, 1970)
On October 3, 1968, the Armed Forces of Peru took over, exactly twenty years after the coup that overthrew the Bustamante government and installed an oligarchic regime protected by armed forces. But this time, the military coup is only partially part of the traditional political picture. The change that took place in the Armed Forces between the coup of 1948 and the institutional coup of 1968, is inserted within the social transformations that the country has experienced in that period. These transformations have modified the framework of social and power relations, diversifying them and unleashing new forces that are impossible to control under traditional mechanics.